Resveratrol-loaded nanoemulsion prevents cognitive decline after abdominal surgery in aged rats - Fabricio M. Locatelli; Takashi Kawano; Hideki Iwata; Bun Aoyama; Satoru Eguchi; Atsushi Nishigaki; Daiki Yamanaka; Hiroki Tateiwa; Marie Shigematsu-Locatelli; Masataka Yokoyama (Elsevier, 2018)
The maladaptive response of aged microglia to surgery and consequent neuroinflammation plays a key pathogenic role in postoperative cognitive dysfunction (POCD). Here, we assessed the preventive effect of resveratrol (RESV) for POCD in aged rats. The emulsified form of RESV (e-RESV) was selected to improve its oral and brain bioavailability. Animals were assigned to one of four groups: e-RESV (80 mg/kg) versus vehicle treatment by abdominal surgery versus isoflurane anesthesia alone (n = 8 in each group). The dose-dependent effects of e-RESV were also assessed in dose range of 0-60 mg/kg. Either vehicle or e-RESV was administered intragastrically 24 h before surgery. Seven days after procedure, cognitive function was evaluated using a novel object recognition test, followed by measurement of hippocampal pro-inflammatory cytokine levels. Our results showed that pre-treatment with e-RESV attenuated the surgery-induced cognitive impairment and related hippocampal neuroinflammation at 40 mg/kg or higher doses. Additionally, the ex-vivo experiments revealed that the preemptive e-RESV regimen reduced the hippocampal microglial immune reactivity to lipopolysaccharide. Furthermore, e-RESV induced neuroprotective benefits were inhibited by the concomitant administration of sirtinol, a specific SIRT1 inhibitor. Our findings imply the preventive potential of e-RESV for POCD via the SIRT1 signaling pathway. Keywords: Resveratrol, Neuroinflammation, Postoperative cognitive dysfunction, Microglia